(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2026)
Background: Cervical cancer remains a significant public health challenge, particularly in low-resource settings. Despite the high burden of cervical intraepithelial neoplasia (CIN) and invasive cancer in Bangladesh, data on disparities between tribal and non-tribal populations in the Chittagong Hill Tract (CHT) region remain scarce. Objective: This study aimed to compare the patterns and associated factors of CIN and invasive cervical carcinoma among tribal and non-tribal VIA-positive women undergoing colposcopy evaluation. Methods: A cross-sectional study was conducted at Bandarban district hospital in CHT, including 284 VIA-positive women. Colposcopic evaluation with guided biopsy was performed, and histopathological findings were categorized as normal, CIN1, CIN2, CIN3, or invasive carcinoma. Sociodemographic and reproductive factors were analyzed for associations. Results: Non-tribal women exhibited higher educational attainment but married earlier and delivered their first child at younger age compared to tribal women (p<0.05). Colposcopy revealed a healthy cervix in 51.4% (146/284), while CIN I, CIN II, CIN III, and invasive carcinoma were detected in 34.9%, 9.9%, 1.4%, and 2.5% of cases, respectively. No significant differences in colposcopy findings were observed between tribal and non-tribal groups (p<0.05). Paradoxically, women marrying after 18 years demonstrated a higher frequency of abnormal findings (p = 0.030) compared to those married younger. Conclusion: While tribal and non-tribal women showed comparable cervical abnormality rates despite sociodemographic disparities, the unexpected association between later marriage and higher abnormality prevalence warrants further investigation. Bangladesh J Obstet Gynaecol, 2025; Vol. 40(2): 84-90